Serum prolactin levels and its clinical correlates in women presenting with infertility at the gynaecologic clinic of a tertiary hospital in North-central Nigeria - Julius Kolajo Dare; Tola Yinka Bakare; Grace Ezeoke; Muideen Gbenga Adesola; Hafeez Ayotunde Salawu; Kikelomo Temilola Adesina; Abiodun Akanbi Gafar Jimoh; Sikiru Abayomi Biliaminu (Babcock University Medical Journal)
Objectives: We aimed to determine and compare the serum prolactin levels in infertile women and fertile controls and to compare the clinical presentations such as menstrual disorders, and visual field defects to prolactin levels in both groups.